2015
DOI: 10.7309/jmtm.4.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Apps- will they be a Facelift for Today's Medical/Dental Practice?

Abstract: Background: With the recent advent of smart phones, usage of medical apps is on rise. Smart phones are powerful devices that combine the conventional functions of a mobile phone with advanced computing capabilities enabling users to access software applications commonly termed as ''apps''. Health care applications (apps) that are downloadable on to smart phones are increasingly becoming popular among clinicians. Aim:The aim of the present study was to assess the usage of health care apps among Medical and Dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Anatomy and physiology are required by most physician's assistant, physical therapy, nursing, medical and dental programs. The use of mobile technologies and apps in the health professions has increased dramatically in recent years so the introduction of these apps can only help to better prepare the students for their careers (Vafa and Chico, ; Zheng et al, ; Jasti et al, ; Rubenstein and Schubert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy and physiology are required by most physician's assistant, physical therapy, nursing, medical and dental programs. The use of mobile technologies and apps in the health professions has increased dramatically in recent years so the introduction of these apps can only help to better prepare the students for their careers (Vafa and Chico, ; Zheng et al, ; Jasti et al, ; Rubenstein and Schubert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Applications are not only used by the common person, but also proved useful among the healthcare specialists as well. A study by Jasti et al (2015) suggested that medical and dental health professionals used smartphone apps for knowledge purpose (58.8%) and patient education purpose (41.4%) as well [5]. This suggests that apps serve as knowledge providers and for spreading awareness through patient education.…”
Section: Use Of Applications Among Healthcare Professionalsmentioning
confidence: 99%
“…Dentists too are getting involved in this technological revolution. In a descriptive study by Jasti et el., 9 approximately 68% of the surveyed dentists from Khammam, Andhra Pradesh reported using healthcare apps on their smartphones for either personal knowledge or patient education purposes. In a Dental Public Health setting, mobile phones can be used for primordial, primary, secondary, as well as tertiary prevention.…”
Section: Applying Mobile Phones In Dental Public Healthmentioning
confidence: 99%